THE EFFECTIVENESS OF WOODEN BALL TO INTRODUCE BASIC COLORS TO THE STUDENTS WITH LIGHT MENTAL RETARDATION IN CLASS D1/C OF SLB FAN REDHA PADANG (Single Subject Research) - Windi Pratama; Marlina Marlina; Damri Damri (Universitas Negeri Padang, 2015)
Abstract: This research discussed about the effectiveness of wooden ball to introduce basic colors to the students with light mental retardation in class D1/C of SLB Fan Redha Padang. The aim of this research was to prove whether the use of wooden ball was effective to introduce basic colors to the student with light mental retardation in class D1/C of SLB Fan Redha Padang. The subjects of the research was a student with light mental retardation in class D1/C of SLB Fan Redha PadangThis was a single subject research which was intended to see the direction of graphic tendency comparing between baseline condition and treatment condition. The data were gathered through direct observation. They were recorded on the student worksheet in which the researcher tallied on colors read correctly by the student. The data gotten then was analyzed by using Visual Analysis of GraphicBased on the results of the research it was concluded that the use of wooden ball could improve the student’s ability to recognize basic colors significantly. This could be seen from the result of within and inter-condition analysis indicating that the direction of tendency and tract of data improved. The percentage of the data overlapped was 0%. In baseline condition (A1), the student’s ability to recognize the colors was 0. In intervention condition (B), the student was able to recognize three colors, and in baseline condition (A2) the student was able to recognize three colors. After the treatment given, the student’s ability to recognize colors improved in which she should mention three colors correctly. It was suggested to the teachers to use wooden ball in the learning process to improve the ability of the student with light mental retardation to recognize color. Keywords: Playing ball wood, Basic color, Mentally retarded